STRATEGIES FOR IMPROVING THE PHYSICOCHEMICAL PROPERTIES OF DIESEL FUEL - Karimova S.A., (Ustozlar uchun, 2025)
Annotation. Diesel fuel is a vital energy source widely used in transportation, industry, and agriculture. Its physicochemical properties—such as viscosity, density, cetane number, sulfur content, volatility, and oxidative stability—directly influence engine performance, fuel efficiency, emissions, and durability. Over the years, the demand for cleaner, more efficient diesel fuels has prompted extensive research into modifying and improving these properties. The primary objective is to enhance fuel performance while minimizing environmental impact and complying with increasingly stringent regulations.